2020
DOI: 10.1126/science.abe4747
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and multivalent nanobodies efficiently neutralize SARS-CoV-2

Abstract: Cost-effective, efficacious therapeutics are urgently needed against the COVID-19 pandemic. Here, we used camelid immunization and proteomics to identify a large repertoire of highly potent neutralizing nanobodies (Nbs) to the SARS-CoV-2 spike (S) protein receptor-binding domain (RBD). We discovered Nbs with picomolar to femtomolar affinities that inhibit viral infection at sub-ng/ml concentration and determined a structure of one of the most potent in complex with RBD. Structural proteomics and integrative mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
426
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(471 citation statements)
references
References 63 publications
(36 reference statements)
28
426
0
Order By: Relevance
“…Overall, our analysis suggests that a loss in mAb efficacy by the mutations may be alleviated by combination treatments consisting of mAbs that bind alternative, non-overlapping epitopes and act via different neutralization mechanisms to block virus mutational escape (Baum, et al, 2020;Hansen, et al, 2020;Marovich, et al, 2020;Xiang, et al, 2020) . A potential approach to minimize the impact of mAb escape mutations is indeed to develop additional mAbs with epitopes that are highly resistant to viral escape, such as those that include epitopes outside of the RBD and epitopes that are cross-reactive across SARS-CoV and SARS-CoV-2, indicating conserved epitopes with low tolerance for mutation (Pinto, et al, 2020;Wec, et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Overall, our analysis suggests that a loss in mAb efficacy by the mutations may be alleviated by combination treatments consisting of mAbs that bind alternative, non-overlapping epitopes and act via different neutralization mechanisms to block virus mutational escape (Baum, et al, 2020;Hansen, et al, 2020;Marovich, et al, 2020;Xiang, et al, 2020) . A potential approach to minimize the impact of mAb escape mutations is indeed to develop additional mAbs with epitopes that are highly resistant to viral escape, such as those that include epitopes outside of the RBD and epitopes that are cross-reactive across SARS-CoV and SARS-CoV-2, indicating conserved epitopes with low tolerance for mutation (Pinto, et al, 2020;Wec, et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Here, we examined 11 mAbs (Table 1) reported to have neutralizing effects on wt virus, including two Abs used in the Regeneron combination Ab therapy that has been granted emergency use authorization. Five mAb binding epitopes (Epitope I to V) on the SARS-CoV-2 RBD have been identified, residues E484 and K417 contributing to Epitopes I and II (Xiang, et al, 2020). These two charged residues play an essential role in binding many mAbs by forming interfacial salt bridges with oppositely charged spike residues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of these neutralizing antibodies bind to epitopes in the RBD; several also bind to the NTD (Table 2). Epitope mapping and crystal structure studies of the antibodies revealed various binding sites in the RBD (Brouwer et al, 2020;Hansen et al, 2020;Huo et al, 2020;Ju et al, 2020;Pinto et al, 2020;Robbiani et al, 2020;Rogers et al, 2020;Seydoux et al, 2020;Shi et al, 2020;Wan et al, 2020a;Wu et al, 2020c;Xiang et al, 2020;Zost et al, 2020). Some neutralizing antibodies bind to the ACE2 interaction sites on RBD, therefore sterically hindering viral engagement, while others bind to non-ACE2 interacting areas on RBD.…”
Section: Neutralizing Monoclonal Antibodies To Sars-cov-2mentioning
confidence: 99%
“…Although they can use a more diverse VH-gene pool, class 2 antibodies include VH1-2 germline restricted antibodies that form a second commonly elicited multi-donor class of public antibodies 17 . The RBD is also the target of several nanobodies/sybodies that are being considered for clinical development 18,19 .…”
Section: Introductionmentioning
confidence: 99%